The impact of digital finance on the natural resource market: Evidence from DeFi, oil, and gold. (December 2022) - Cevik, Emrah Ismail; Gunay, Samet; Zafar, Muhammad Wasif; Destek, Mehmet Akif; Bugan, Mehmet Fatih; Tuna, Fatih
Abstract: The purpose of this study is to examine the interconnectedness between DeFi and natural resource assets in terms of return and volatility spillovers, as well as the effectiveness of hedging, utilizing the time and frequency domain causality test and the cross-quantilogram approach. To this end, we take into account the ChainLink (LINK) and Maker (MKR) prices for the DeFi market and use crude oil (WTI) and gold prices as proxies for the natural resources market. For this purpose, we observe the daily period from March 14, 2018, to August 15, 2022, in order to evaluate the portfolio diversification benefits during the Covid-19 epidemic. The findings from the time and frequency domain causality test reveal that the price and risk structure of natural resources such as crude oil and gold are influenced by digital finance instruments, particularly during times of crisis. Moreover, the results of the cross-quantilogram approach indicate that the significant cross-correlations between DeFi tokens and natural resource markets during bearish market periods are generally negative therefore DeFi tokens can provide effective hedging for gold and crude oil investors. Highlights: The paper examines the interconnectedness between DeFi and natural resource assets such as crude oil and gold. The market value of the global Fintech ecosystem is predicted to exceed 324 trillion by 2026. We employ the frequency domain causality test and the cross-quantilogram approach. The test results reveal that there is a return and volatility spillover from digital finance instruments to gold and oil. DeFi tokens can provide hedging effectiveness for gold and crude oil investors.